1999
DOI: 10.1007/s003300050900
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CT scan for the diagnosis of chest wall tuberculosis

Abstract: The objective of this study was to determine the utility of CT scan findings for the diagnosis of chest wall tuberculosis, excluding the spine. We reviewed 15 patients (13 Africans and 2 Indians) with chest wall tuberculosis, retrospectively. The radiologic examination consisted of a plain X-ray and a CT scan of the chest for each patient. The site of disease was the rib in 13 patients or the body of the sternum in 2 patients. One rib was involved in 11 patients, 2 contiguous ribs (one site) in 2 patients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 9 publications
(13 reference statements)
1
26
0
3
Order By: Relevance
“…X-ray in the evaluation of bone involvement, it is significantly superior in the evaluation of perilesional soft tissues, mediastinal involvement and pulmonary involvement. (5)(6)(7)(8)(9) Magnetic resonance imaging is a good option for the evaluation of soft tissues and bone lesions, revealing early alterations in the bone marrow, especially at early stages with normal X-ray findings. (4,5,9) Technetium triphasic scintigraphy has high sensitivity and specificity for the diagnosis of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray in the evaluation of bone involvement, it is significantly superior in the evaluation of perilesional soft tissues, mediastinal involvement and pulmonary involvement. (5)(6)(7)(8)(9) Magnetic resonance imaging is a good option for the evaluation of soft tissues and bone lesions, revealing early alterations in the bone marrow, especially at early stages with normal X-ray findings. (4,5,9) Technetium triphasic scintigraphy has high sensitivity and specificity for the diagnosis of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…(6) These findings, which are not exclusive to sternal TB, can be found in aggressive infections such as actinomycosis. (8) Although CT does not appear to have any advantage over sternum prophylaxis in open heart surgery candidates with a history of TB or contact with TB is not indicated due to the rarity of the infection. (9) In our patient, treatment with regimen I resulted in clinical improvement and better cicatrization of the sternal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologically, computed tomography (CT) scan is helpful in anatomical localization, bone and joint involvement and soft tissue abnormalities. Khalil et al suggested the utility of CT in the diagnosis of chest wall TB and described ring enhancing hypodense soft tissue lesion [15]. Magnetic Resonance Imaging (MRI) holds good in places for detection of early marrow and soft tissue involvement due to high contrast resolution of MRI.…”
Section: Discussionmentioning
confidence: 99%
“…[4,6] The rarity of the occurrence of sternoclavicular arthritis was attributed to the peculiar blood supply of the joint. [7] Sternoclavicular joint tuberculosis can present as painful swelling alone or discharging sinus.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The sternum, ribs, and the sternoclavicular joints are uncommonly affected. [3,4] DOI: http://dx.doi.org/10.22192/ijcrbm.2018.03.07.001…”
Section: Introductionmentioning
confidence: 99%